The children's atlas of people & places - Wood, Jenny (Brookfield, Ct. : Millbrook Press, 1993)
Maps, facts, and illustrations present the diverse places and people on our planet.
Includes index.
6.5
3-6
3-6
Booklist
Library Talk
Keywords: Children's atlases; Atlases; Atlases